Posições-sujeito na escrita de língua inglesa como língua adicional: os discursos do período pandêmico - RIBEIRO, André Felipe (2023)
The writing of additional language demands from the individual an organization of his linguistic knowledge in order to interact socially. In this process, however, the writer not only communicates through writing, but “inscribes” himself in positions in which he places himself as a subject so that, from this “unconscious inscription”, it is possible to analyze a discursive functioning. Based on this discussion, this research, of a qualitative nature, aimed to analyze how the discourses of subject positions work in the conditions of the COVID-19 pandemic materialized in enunciates in digital writing by students of advanced level of English as an additional language. The research methodology consisted of collecting and analyzing responses given to an activity in the SUMMIT 1A book by English students at the advanced level of the extension course “Núcleo de Cultura Linguística” linked to the Federal University of Maranhão. Initially, we made an approach on the subject category until we reached how it is understood by the French Discourse Analysis. Then, we base the discussion based on linguistic modalities (CULIOLI, 1978; LE QUERLER, 1996; NEVES, 2006; FUCHS, 1984), on the notion of imaginary formulations (PÊCHEUX, 1969) and on the enunciative analysis of Foucault (2008), specifically with regard to the enunciative description in the work “Arqueologia do Saber”. Furthermore, we approach writing in the digital form, referring to the discourse digitality (DIAS, 2016) in the pandemic context. Subsequently, we made a methodological description, detailing the stages of the research: on the collection of material, the extension project and the reasons for choosing the advanced level of the English course. Afterwards, we describe the criteria for selecting the statements in our corpus, which took into account the discourses that circulated under the conditions of the pandemic; the school material (SUMMIT 1A), whose third edition is from 2017; and the activity answered by the students, coming from the Workbook of the book edition. Soon after, we analyzed the corpus, starting with the description of the linguistic modalities – assertoric, epistemic, appreciative and intersubjective – of the enunciates in view of the enunciative situation of the pandemic. Then, we approach the enunciates from the notions of Rarity, Exteriority and Accumulation proposed by Foucault (2008) in the enunciative description in his work “The Archeology of Knowledge”. Further on, we made a description of the discourses understood in the corpus, as well as their projected subject positions in English language writing. The results of the analyzes described and demonstrated that the enunciations (re)produced in the students' writing brings out denialist discourses interdiscursively about vaccination against COVID-19, about climate and environmental issues, about wearing mask and even about sphericity of the earth, which project equally negationist subject positions, while we observe subject positions defending vaccination and science in which the functioning of these discourses guides the linguistic choices made in the writing process, modalizing their statements and, therefore, reaching and taking part of the writing of English language as an additional language.